Incidence and outcomes of long QTc in acute medical admissions. Issue 11 (17th September 2018) - Mahmud, Rahel; Gray, Adam; Nabeebaccus, Adam; Whyte, Martin Brunel
Summary: Aims: Prolonged QT interval on electrocardiogram (ECG) increases the risk of ventricular arrhythmia. Patients admitted to acute medical units (AMU) may be at risk of QT prolongation from multiple, recognised risk factors. Few data exist regarding incidence or outcomes of QT prolongation in acute general medical admissions. The aims were to determine the incidence of Bazett's‐corrected QT (QTc) prolongation upon admission to AMU; the relationship between QTc and inpatient mortality, length of stay and readmission; proportion with prolonged QTc subsequently administered QT interval‐prolonging drugs. Methods: Retrospective, observational study of 1000 consecutive patients admitted to an AMU in a large urban hospital. Exclusion criteria: age <18 years, ventricular pacing, poor quality/absent ECG. QTc determined manually from ECG obtained within 4‐hours of admission. QTc prolongation considered ≥470 milliseconds (males) and ≥480 milliseconds (females). In both genders, >500 milliseconds was considered severe. Study end‐points, (a) incidence of QTc prolongation at admission; (b) inpatient mortality, length of stay and readmission rates; (c) proportion with QTc prolongation subsequently administered QT interval‐prolonging drugs. Results: Of 1000 patients, 288 patients were excluded, therefore final sample was n = 712. Patient age (mean ± SD) was 63.1 ± 19.4 years; females 49%. QTc prolongation was present in n = 50 (7%) at admission; 1.7% had QTc interval >500 ms. Of the 50 patients admitted with prolonged QTc, 6 (12%) were subsequently administered QT interval‐prolonging drugs. QTc prolongation was not associated with worse inpatient mortality or readmission rate. Length of stay was greater in those with prolonged QTc, 7.2 (IQR 2.4‐13.2) days vs 3.3 (IQR 1.3‐10.0; P  =   0.004), however, in a regression model, presence of QTc did not independently affect length of stay. Conclusions: QTc interval prolongation is frequent among patients admitted to AMU. QT interval‐prolonging drugs are commonly prescribed to patients presenting with prolonged QTc but whether this affects clinical outcomes is uncertain.